1999
DOI: 10.1038/sj.onc.1202535
|View full text |Cite
|
Sign up to set email alerts
|

Truncation of the TGF-β type II receptor gene results in insensitivity to TGF-β in human gastric cancer cells

Abstract: The transforming growth factor-b (TGF-b receptor system has been implicated in the development of resistance to the growth-inhibitory e ects of TGF-b. It has been reported that resistance to TGF-b correlates with inactivation of the TGF-b type II receptor (RII). In the present report, we examine the genetic changes in the TGF-b RII gene of human gastric cancer cell lines, SNU-5 and SNU-668, which we had previously reported to express truncated TGF-b RII transcripts. By independent PCR and Southern hybridizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 21 publications
2
26
0
Order By: Relevance
“…All the members of the TGF-␤ family, including activins and BMPs transduce their signal through a set of type I and type II receptors (49). Truncated type II receptors (50) or soluble type II receptors for TGF-␤ (13) display dominant negative activities. These data suggest that soluble type I receptors for TGF-␤ family members could be used to mimic the biological actions of these cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…All the members of the TGF-␤ family, including activins and BMPs transduce their signal through a set of type I and type II receptors (49). Truncated type II receptors (50) or soluble type II receptors for TGF-␤ (13) display dominant negative activities. These data suggest that soluble type I receptors for TGF-␤ family members could be used to mimic the biological actions of these cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Among nine gastric cancer cell lines, SNU-16, SNU-620 and SNU-719 retained TGF-b sensitivity. SNU-5 and SNU-668 cell lines demonstrated deletion of the TbRII gene (Yang H-K et al, 1999). A frameshift mutation affecting a 10-base pair (bp) polyadenine repeat that is Step RT-PCR was performed using 100 ng of total RNA isolated from SNU-1, SNU-5, SNU-484, and SNU-638 cells.…”
Section: Smad3 Protein Expression In Primary Human Gastric Cancer Tismentioning
confidence: 99%
“…More specifically, in vitro studies of epithelial cells have shown TGF-b can decrease cdk4 and cyclin D1 expression and can increase the protein levels of p15, p21 and p27. [22][23][24][25][26][27][28][29][30] TGF-b has also been shown in in vitro systems to affect cell proliferation by inhibiting the phosphorylation of Rb, p107 and p130, presumably through the regulation of cdk2 and cdk4 kinase activity, and to affect the expression of a variety of proteins involved in cell proliferation, including c-myc, cdc25a and E2F. [31][32][33] Thus, in vitro studies of epithelial cells demonstrate that TGF-b can regulate cell cycle progression through a variety of different mechanisms that are contextually specific, and that through these mechanisms TGFBR2 could act to suppress colon cancer formation.…”
mentioning
confidence: 99%